2023
DOI: 10.3390/brainsci13010104
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Neural Cellularity to the Influence of Low Educational Level

Abstract: Background: Education is believed to contribute positively to brain structure and function, as well as to cognitive reserve. One of the brain regions most impacted by education is the medial temporal lobe (MTL), a region that houses the hippocampus, which has an important role in learning processes and in consolidation of memories, and is also known to undergo neurogenesis in adulthood. We aimed to investigate the influence of education on the absolute cell numbers of the MTL (comprised by the hippocampal form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…50 However, no difference was found, indicating that the number of neurons in this region probably is not affected by formal education. 48 Nevertheless, there is at least one study using MRI that showed more gray matter in bilateral angular, dorsal occipital, middle temporal, left supramarginal, and superior temporal gyri in late literates (individuals who learned to read as adults) than in illiterates. 42 But the authors of that paper did not suggest an explanation for the phenomenon.…”
Section: Learning To Read and Brain Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…50 However, no difference was found, indicating that the number of neurons in this region probably is not affected by formal education. 48 Nevertheless, there is at least one study using MRI that showed more gray matter in bilateral angular, dorsal occipital, middle temporal, left supramarginal, and superior temporal gyri in late literates (individuals who learned to read as adults) than in illiterates. 42 But the authors of that paper did not suggest an explanation for the phenomenon.…”
Section: Learning To Read and Brain Developmentmentioning
confidence: 99%
“…To verify whether learning to read increases neurogenesis in the hippocampus, 48 we investigated the number of neurons in the medial temporal lobe of the hippocampal region of brains of men without cognitive decline from our brain bank. 49 A comparison was made between brains of individuals with very low formal education (0–4 school years) versus those with higher formal education (≥8 school years).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation